Perception of Pre-service Teachers about their Preparation for Inclusive School in Pakistan - Farah Naz,Maimona Ijaz (JIE, 2024)
A professional teacher, prepared through an effective teacher education program is the major agent for successful inclusive practices. The study examined the perceptions, skills, and knowledge of pre-service teachers on inclusion and challenges faced during teaching in an inclusive classroom. I